Systemic Inflammatory Reaction in Operative Gynecological Care - A. V. Pronoza; V. T. Dolgikh; V. N. Lukach (Общая реаниматология)
Objective: to evaluate the impact of various methods of anesthesia and treatment on the development of a systemic inflammatory reaction (SIR) in gynecological patients. Subjects and methods. The manifestations of SIR were studied in 426 patients who had undergone standard operations on the uterine appendages via traditional laparoscopic access. Ninety-seven women had unoptimized anesthetic maintenance and postoperative preventive antibacterial therapy (Group 1); 95 women had unop-timized anesthetic maintenance and pre- and postoperative massive antibacterial therapy (Group 2); 103 women had optimized anesthetic maintenance and preventive antibacterial therapy (Group 3); 131 women had optimized anesthetic maintenance and massive antibacterial therapy (Group 4). Results. Antibacterial therapy was not found to affect the manifestations of SIR significantly. The optimized anesthetic maintenance that differed from the unoptimized one in higher nociceptive defense had a considerable impact on the manifestation of SIR. Low molecular-weight heparins and preoperative hyperv-olemic hemodilution with hydroxyethyl starch preparations positively affected the study indices. The observed SIR belonged to the second stage of release of the small amount of mediators into systemic circulation. The transition of SIR to the third stage of inflammatory reaction generalization was suggested by changes in other monitored parameters, simultaneously informing about this or that degree of multiple organ dysfunction. Conclusion. Laparoscopic surgical intervention, multicom-ponent preoperative sedation, preventive preoperative analgesia with nonsteroidal anti-inflammatory drugs, prevention of microcirculatory disorders with low molecular-weight heparins, preoperative hypervolemic hemodilution with hydroxyethyl starch, and use of the loading doses of opioids in the period of induction to anesthesia in combination with propofol lower the level of a systemic inflammatory response in the early postoperative period. Key words: operative gynecology, systemic inflammatory reaction, anesthetic maintenance.